Homozygous mutations in VAMP1 cause a presynaptic congenital myasthenic syndrome. Issue 4 (29th March 2017) - Salpietro, Vincenzo; Lin, Weichun; Vedove, Andrea Delle; Storbeck, Markus; Liu, Yun; Efthymiou, Stephanie; Manole, Andreea; Wiethoff, Sarah; Ye, Qiaohong; Saggar, Anand; McElreavey, Kenneth; Krishnakumar, Shyam S.; et al.
Abstract : We report 2 families with undiagnosed recessive presynaptic congenital myasthenic syndrome (CMS). Whole exome or genome sequencing identified segregating homozygous variants in VAMP1 : c.51_64delAGGTGGGGGTCCCC in a Kuwaiti family and c.146G>C in an Israeli family. VAMP1 is crucial for vesicle fusion at presynaptic neuromuscular junction (NMJ). Electrodiagnostic examination showed severely low compound muscle action potentials and presynaptic impairment. We assessed the effect of the nonsense mutation on mRNA levels and evaluated the NMJ transmission in VAMP1 lew/lew mice, observing neurophysiological features of presynaptic impairment, similar to the patients. Taken together, our findings highlight VAMP1 homozygous mutations as a cause of presynaptic CMS. Ann Neurol 2017;81:597–603